A Review of Urban Water Body Challenges and Approaches: (2) Mitigating Effects of Future Urbanization. Issue 1 (24th January 2014) - Hughes, Robert M.; Dunham, Susie; Maas‐Hebner, Kathleen G.; Yeakley, J. Alan; Harte, Michael; Molina, Nancy; Shock, Clinton C.; Kaczynski, Victor W.
Abstract: Previously we examined how degraded urban streams can be rehabilitated, with emphasis on identifying solutions that match the scale of the problems (Hughes et al. 2014). Our findings showed that rehabilitation techniques are challenging but that some environmental benefits can nearly always be obtained regardless of existing conditions. Although rehabilitation is useful in many present‐day situations, biologists need to consider the future and think about ways of preventing or reducing future environmental damage. We need to reduce future damage because urban areas are likely to expand greatly over the next century; if historical patterns continue, the number and length of streams experiencing urban stream syndrome will increase, with resulting high repair costs. However, there are several ways of avoiding or mitigating damage that are not only cost effective but provide benefits to humans and urban ecosystems.